RELACIJE IZMEĐU BRZINE TRČANJA U KRIVINI I NAGIBA TELA - Pavle Opavski (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The most natural form of human moving is running. The most common form of running is the one in a bee-line at the area without inclination. This form is realized by a successive activity of the moving mechanism in the line. There is a stereotype described in the symmetric Central Nervous System. In a case that direction should be changed, this complex form of moving become more complicated. Moving is asymmetrical now, the amplitude of extremity move in one side is not in accordance with the other one. The muscles of the one side neither function in the same direction nor with the same intensity like the ones at the other side. The change of direction is the result of the body's inclination. The aim of this study is to show quantitative relation between the angle of body's inclination and the running speed in a turn.